INDONESIAN SMES FINANCIAL QUALITY INFORMATION PERFORMANCE AS LEARNING ORGANIZATION - Uswatun Khasanah; Dewi Puspaningtyas Faeni; Rachmat Pramukty; Amor Marundha; Tri Yulaeli (Jurnal Ilmiah Manajemen Ubhara, 2022)
SMEs comprise of majority of registered small medium enterprises in the developing countries. They play an important economic role by generating income and employment by contributing significantly to export earnings. Unfortunately, SMEs are not bankable, banks tend to prioritize lending to large companies because of higher risks and high transaction and monitoring cost of SME lending activities. This research observed access to finance support to tourism travel industry in Indonesia. Research location was in Borobudur Temple which located in Magelang City. The temple has attracted many visitors both domestic and international visitors. The temple has become one of the world’s seven wonders and visitor attractions that bring the values of religious harmony and natural human beauty surrounded by towering mountains visited by local and foreign visitors. It was concluded that Financial Information Quality to Bank Accessibility and Performance of SMEs In Asean Economic Community. Keywords : Finance Support, Tourism Travel Industry and SMEs